Antioxidant Activity and Neuroprotective Role of Docosahexaenoic Acid (DHA) Supplementation in Eye Diseases That Can Lead to Blindness: A Narrative Review - María Lafuente; María Elena Rodríguez González-Herrero; Stéphanie Romeo Villadóniga; Joan Carles Domingo (MDPI AG, 2021)
The objective of this narrative review is to provide updated evidence, based on data from experimental and clinical studies, of the prominent role of omega-3 polyunsaturated fatty acids (n-3 PUFAs) for a number of crucial mechanisms involved in counteracting cell damage induced by oxidative stress in eye diseases. This article is focused on the antioxidant and neuroprotective effects of docosahexaenoic acid (DHA), which have been assessed in different experimental models and clinical studies, particularly in proliferative diabetic retinopathy, age-related macular degeneration and glaucoma that are the most common eye diseases leading to severe vision loss. The mechanisms involved in the role of DHA in protecting human retinal pigment epithelial cells from oxidative stress as well as the interaction with glutathione (GSH) are also described. The review is intended to provide novel and salient findings supporting the rationale of the use of dietary supplementation with high-dose DHA (1050 mg/day) in the form of triglyceride as a potent antioxidant compound for improving the eye health. However, the overall clinical evidence for the use of dietary strategies based on supplementation with n-3 PUFAs in eye diseases linked to oxidative stress other than high-dose DHA triglyceride is both limited and inconsistent.